Identification and Analysis of the Tegument Protein and Excretory-Secretory Products of the Carcinogenic Liver Fluke Clonorchis sinensis - Shi, Yunliang; Yu, Kai; Liang, Anli; Huang, Yan; Ou, Fangqi; Wei, Haiyan; Wan, Xiaoling; Yang, Yichao; Zhang, Weiyu; Jiang, Zhihua (Frontiers in Microbiology, 2020)
Liver fluke proteins, including excretory-secretory products (ESPs) and tegument proteins, are critical for the pathogenesis, nutrient metabolism, and the etiology of liver cancer and the immune response to it. To understand the protein function in Clonorchis sinensis physiology and human clonorchiasis, the ESP and tegument proteins of C. sinensis have been identified. Supernatants containing ESPs from adult C. sinensis in culture for 6 h were harvested and concentrated. The tegument was detached using a freeze/thaw method and extracted with succession extraction buffers . The outer surface proteins of C. sinensis were labeled with biotin, and the biotinylated proteins were purified. The ESP proteins, tegument proteins and outer surface labeling proteins were identified and analyzed by high-resolution LC-MS/MS. The identified proteins were compared with those of other flukes, and the protein functions associated with pathogenesis, carcinogenesis and potential vaccine antigens and drug targets were predicted and analyzed. A total of 175 proteins were identified from the 6-h culture of C. sinensis ESPs. A total of 352 tegument proteins were identified by sequential solubilization of isolated teguments, and a subset of these proteins were localized to the surface membrane of the tegument by labeling them with biotin, and 30 identified proteins, including annexins, actin and tetraspanins, were potential immunomodulators and promising vaccine antigens. Interestingly, in the 352 tegument proteins, as many as 155 were enzymes, and most were oxidoreductases, hydrolases or transferases. A comparison of the outer surface proteins of C. sinensis with those of other flukes indicated that flukes have some common outer surface proteins, such as actin, tetraspanin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and annexin. In the C. sinensis proteome, the proteins granulin, thioredoxin peroxiredoxin, carbonyl reductase 1 and cystatin were identified and predicted to be related to liver disease and cancer. The proteome discovery of C. sinensis could contribute to the understanding of complex parasite-host relationships, improve the diagnosis of clonorchiasis and benefit research on the pathogenesis and development of novel interventions, drugs and vaccines to control C. sinensis infection.